Coordinated regulation of hormone-sensitive lipase and lipoprotein lipase in human adipose tissue in vivo: implications for the control of fat storage and fat mobilization. - Frayn, K; Coppack, S; Fielding, B; Humphreys, S (1995)
The enzymes lipoprotein lipase (LPL, EC 3.1.1.34) and hormone-sensitive lipase (HSL, EC 3.1.1.3) apparently catalyze opposing functions in white adipose tissue: the former is concerned with fat storage, the latter with fat mobilization. We have studied their regulation in vivo in normal subjects in the postabsorptive state and after eating meals of different compositions, by measurement of arteriovenous concentration differences for triacylglycerol, non-esterified fatty acids and glycerol across a subcutaneous adipose depot. The two enzymes are regulated in a broadly reciprocal manner: in the overnight-fasted state, HSL is more active, but after a meal HSL is suppressed whilst LPL is activated. The movement of fatty acids in and out of adipose tissue appears to be driven by concentration gradients generated by regulation of these two enzymes, and also by activation, in the postprandial period, of the process of fatty acid esterification. The results show some interesting and perhaps unexpected features of metabolic regulation. Of the fatty acids generated by the action of LPL on circulating TAG, a large proportion is released directly into the venous plasma: close to 100% in the overnight-fasted state, and 50% or more at the peak of LPL action after a meal, making what appear reasonable assumptions. We suggest that this apparent 'inefficiency' of fat storage reflects the energetic cost of maintaining precise control over such a fundamental process. Although LPL is usually thought of as the enzyme regulating fat deposition, in fact the fatty acids and glycerol it releases from circulating TAG represent a substantial proportion of those released from adipose tissue, especially in the postprandial state. In addition, although HSL is considered the enzyme responsible for fat mobilization, suppression of its activity is essential to normal regulation of fat deposition. Thus, fat storage and fat mobilization during normal daily life are controlled by coordinated regulation of a number of enzymatic processes in white adipose tissue.